Aplicação da lógica fuzzy no controle da cristalização de um sistema de refrigeração por absorção com par brometo de lítio - Marques, João Erivando Soares (2010)
This work presents theoretical and experimental study of a system of control for a steam generator. This system was developed to control the crystallization of a cooling system for absorption. The control system maintains the pressure generator above the zone of crystallization of diagram temperature pressure-saturated solution concentration of LiBr-water. The control is accomplished through simultaneous use of the relay and the frequency converter. The frequency converter acts in engine speed of pump firing of condenser cooling tower, while the relay operates directly into the burner of the generator, consecutively in thermal power of combustion. The control system can act in any pressure reference values above the zone of crystallization of absorption cooling system. In the control flow control techniques were used and fuzzy Modeling and control power thermal combustion, on-off control. Ten different experiments were conducted, which proved the efficiency of the system of control.